Pengaruh Konten Personal Branding Akun Instagram @xavieraaputri terhadap Self-Efficacy Generasi Z Kota Banjarmasin - Nabila , Janpy; Muhammad Ainani; Muhammad Alif; Muhammad Nizar Hidayat (Jurnal Nomosleca, 2025)
This study examines the influence of personal branding content on the Instagram account @xavieraaputri on the self-efficacy of Generation Z in Banjarmasin City. Using a quantitative approach with questionnaires and literature study, the research involved 100 respondents selected through the Slovin formula. Data analysis employed descriptive statistics and non-linear exponential regression. Results indicate a strong positive relationship, with a correlation coefficient (R) of 0.857 and coefficient of determination (R²) of 0.735. The adjusted R² of 0.732 and low standard error of 0.083 confirm the model’s reliability. The regression coefficient of 0.020 with a significance level of 0.000 demonstrates a statistically significant influence. These findings suggest that personal branding content on Instagram significantly and positively affects the self-efficacy of Generation Z, highlighting the role of social media self-representation in shaping individual confidence.